Placental Transfer of Vitamin K1 and Its Implications in Fetal Hemostasis - Mandelbrot, L; Guillaumont, M; Leclercq, M; Lefrère, J J; Gozin, D; Daffos, F; Forestier, F (Thrombosis and Haemostasis, 1988)
Vitamin K status was evaluated using coagulation studies and/ or vitamin IQ assays in a total of 53 normal fetuses and 47 neonates. Second trimester fetal blood samples were obtained for prenatal diagnosis under ultrasound guidance. Endogenous vitamin K1 concentrations (determined by high performance liquid chromatography) were substantially lower than maternal levels. The mean maternal-fetal gradient was 14-fold at mid trimester and 18-fold at birth. Despite low vitamin K levels, descarboxy prothrombin, detected by a staphylocoagulase assay, was elevated in only a single fetus and a single neonate.After maternal oral supplementation with vitamin K1, cord vitamin K1 levels were boosted 30-fold at mid trimester and 60 fold at term, demonstrating placental transfer. However, these levels were substantially lower than corresponding supplemented maternal levels. Despite elevated vitamin K1 concentrations, supplemented fetuses and neonates showed no increase in total or coagulant prothrombin activity. These results suggest that the low prothrombin levels found during intrauterine life are not due to vitamin K deficiency.
Keywords: Vitamin K; Placental transfer; Fetal hemostasis; Prothrombin; Descarboxy prothrombin